2018
DOI: 10.3389/fimmu.2018.02564
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo Effects of Lactate on Metabolism and Cytokine Production of Human Primary PBMCs and Monocytes

Abstract: Lactate, the end product of anaerobic glycolysis, is produced in high amounts by innate immune cells during inflammatory activation. Although immunomodulating effects of lactate have been reported, evidence from human studies is scarce. Here we show that expression of genes involved in lactate metabolism and transport is modulated in human immune cells during infection and upon inflammatory activation with TLR ligands in vitro, indicating an important role for lactate metabolism in inflammation. Extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
108
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 35 publications
3
108
1
2
Order By: Relevance
“…Both lactate and pyruvate have been demonstrated previously to exert anti-inflammatory effects. For instance, very recent work demonstrates that addition of lactate to LPS-stimulated primary human monocytes causes a distinct metabolic shift by decreasing aerobic glycolysis and increasing oxidative phosphorylation, a metabolic state characteristic for anti-inflammatory responses [ 24 ]. In the same study, lactate was shown to decrease LPS-induced production of pro-inflammatory cytokines by human PBMCs [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both lactate and pyruvate have been demonstrated previously to exert anti-inflammatory effects. For instance, very recent work demonstrates that addition of lactate to LPS-stimulated primary human monocytes causes a distinct metabolic shift by decreasing aerobic glycolysis and increasing oxidative phosphorylation, a metabolic state characteristic for anti-inflammatory responses [ 24 ]. In the same study, lactate was shown to decrease LPS-induced production of pro-inflammatory cytokines by human PBMCs [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, very recent work demonstrates that addition of lactate to LPS-stimulated primary human monocytes causes a distinct metabolic shift by decreasing aerobic glycolysis and increasing oxidative phosphorylation, a metabolic state characteristic for anti-inflammatory responses [ 24 ]. In the same study, lactate was shown to decrease LPS-induced production of pro-inflammatory cytokines by human PBMCs [ 24 ]. The authors proposed that immunomodulatory effects of lactate may serve as a feedback signal to limit excessive inflammatory responses of highly glycolytic pro-inflammatory immune cells [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its role in lactic acid metabolism and its links to PSA have yet to be clarified, but its role in PSA patients, compared to undifferentiated arthritis patients, has been demonstrated in our study for the first time. In the future, additional study concerning the immune-modulation, glycobiology (22), and inflammation effect (23) of Megasphaera elsdenii is required to establish the relationship between this organism and PSA disease.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially remarkable and somehow surprising, as HIF1Îą is usually considered a pro-inflammatory mediator [ 96 ]. Importantly, studies with primary human monocytes and peripheral blood mononuclear cells have confirmed these observations to be relevant for human macrophages biology as well [ 97 ]. Overall, lactate import in macrophages seems to limit their pro-inflammatory potential.…”
Section: Expression and Importance Of Metabolite Transporters In Mmentioning
confidence: 93%